Open Access Week 2011 in the Czech Republic (Report) - Rygelová, Pavla (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
The awareness of open access is slowly rising in the Czech academic environment. Both green open access and gold open access have broken through thanks to Open Access Week, which has for the second time been organized by twelve Czech university libraries, the National Technical Library, and the Library of the Academy of Sciences of the Czech Republic, under the auspices of the Association of Libraries of Czech Universities.